VISITOR RESPONSES ON TOURIST ATTRACTION BOOMBARA WATERPARK KAMPAR DISTRICT - Gilbert Yosafat Christ Van Doli Manurung; Siti Sofro Sidiq (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2021)
Responses in the world of tourism are income or the perspective of visitors and tourists in undesrtandings a tourist destination. This research was conducted at Boombara Waterpark at street Pasir Putih KM. 5 Desa Baru Kabupaten Kampar Riau, Indonesia. This riset aims to know visitor responses to the tourist attraction of Boombara Waterpark Kabupaten Kampar . This riset uses a quantitative descriptive method, to manage the data obtained in the field through observation, questionnaires and documentation. This riset uses the theory of Suryadana (2015) where an area has a tourist attraction if it has the following characteristics: uniqueness, authenticity, rarity, foster enthusiasm and provide value for tourists. Based on the results of research with those grand theory the results obtained from the sub variable uniqueness are in the agree category, athenticity are in disagree category, rarity are in the agree category, foster enthusiasm and provide value for tourists are in the agree category. Based on the result so visitors responses to the tourist attraction of Boombara Waterpark need to be improved. Keyword: Responses, Attractions